Immuntherapien als moderne Tumortherapien - Grüllich, Carsten (Der Radiologe, 2017)
BackgroundThe specific immune system is capable of preventing the development of tumor diseases and stimulation of cytotoxic T‑lymphocytes can repress existing tumors. The activation of T‑lymphocytes is influenced by a new class of antibody-based medication, the immune checkpoint inhibitors.MethodsReview of the scientific background and the published clinical trials on the activity and approval of immune checkpoint inhibitors for various tumor diseases.ResultsImmune checkpoint inhibitors function by activating T‑lymphocytes during the priming (CTLA4) or effector phase (PDL1/PD1). Activated tumor-specific T‑lymphocytes in turn can attack the tumor. For malignant melanoma, a combination of both checkpoint inhibitors is approved and achieves response rates of 60%. The PD1 inhibitors are active against non-small cell lung cancer achieving a progression-free survival (PFS) of 12 months and a survival rate of 60% at 24 months. For renal cell cancer and bladder cancer response rates to PD-1 inhibitors of approximately 25% and an improvement in overall survival (OS) up to 4 months compared to previous standard therapies have been reported.ConclusionImmune checkpoint inhibitors are active against a number of tumors. In some cases, such as malignant melanoma and non-small cell lung cancer, the response rates are impressive and exceed those achieved with conventional chemotherapies. Future combinations with other treatment modalities, such as chemotherapy and radiotherapy may further improve the response rates.